ROLE OF THE PHARMACIST IN THE DIAGNOSIS, TREATMENT AND PREVENTION OF ENTEROBIOSIS (CIPEEX, 2025)
The objective of this abstract was to reinforce the role of the pharmacist in the diagnosis, treatment, and prevention of enterobiosis. Enterobius vermicularis, commonly known as pinworms, is a widely distributed parasite, particularly prevalent in developing countries, affecting millions worldwide. Children are the primary risk group, especially in environments with inadequate hygiene and high population density. Transmission occurs both directly (person-to-person) and indirectly (via contaminated objects).Adult worms inhabit the large intestine and lay eggs in the perianal area, facilitating the parasite’s spread. While many cases are asymptomatic, heavy infestations can cause anal itching and irritability, with complications such as appendicitis and urinary tract infections in severe cases, particularly in women. Despite the availability of effective antiparasitic treatments, controlling infections remains challenging due to high reinfection rates, compounded by limited access to diagnostics and proper treatment guidance.The pharmacist plays a critical role in early diagnosis, effective treatment, and reinfection prevention. Pharmacists can advise on simple diagnostic methods, such as the adhesive tape test, which reveals eggs with a characteristic D appearance, and promote health education. During treatment, pharmaceutical follow-up ensures proper administration of antiparasitics, improving adherence and therapeutic success, which reduces reinfection. Moreover, pharmacist-led educational programs focused on hygiene practices and environmental control are proven strategies to reduce reinfection rates, particularly in children.
Keywords: enterobiosis; pharmacist; parasites